Biochemical studies on the serum proteins of patients suffering from kwashiorkor - Potgieter, Gideon Muller (Division of Biomedical Engineering, 2020)
This thesis describes the results of cert in biochemical investigations on the serum proteins of patients suffering from the protein depleted state, kvashiorkor.